PENGARUH LITERASI KEUANGAN, ELECTRONIC MONEY, GAYA HIDUP, DAN KONTROL DIRI TERHADAP PERILAKU KONSUMTIF MAHASISWA PADA MASA PANDEMI COVID-19 - Lisdayanti, Dina; Trihantana, Rully; Kusumaningrum, Ria (SAHID BANKING JOURNAL, 2023)
Financial literacy is financial knowledge and financial literacy will help individuals organize personal financial planning, so that individuals can maximize the time value of money and the profits obtained by students will be greater and will improve their standard of living. In this regard, research was conducted on students at the Sahid Bogor Islamic Institute and the Ummul Quro Al-Islami Bogor Institute. This research method uses quantitative methods with multiple regression analysis. The research results show that financial literacy, lifestyle and self-control have a positive effect on students' consumptive behavior during the Covid-19 pandemic, while electronic money has no positive effect on students' consumptive behavior during the Covid-19 pandemic.